Management of Autoimmune Hemolytic Anemia in the Midst of Coronavirus Disease 2019 Pandemic: A Case Report - Kurniawan, Andree; Halim, Devina Adella (Fakultas Kedokteran Universitas Pelita Harapan, 2020)
Introduction : The novel coronavirus disease 2019 (COVID-19) has become a pandemic involving all people and can be severe and life-threatening in a certain population such as those with comorbidity. Autoimmune hemolytic anemia (AIHA) is an autoimmune hematologic disease characterized with antibodies production that binds to red cell surface antigens. In this pandemic, several concerns have been raised by autoimmune disease clinicians and patients regarding the use of immunosuppressive drugs. In this case report, we illustrate the problems of autoimmune hemolytic anemia patient when she got active case.Case Illustration : A 28 years old lady was admitted to the hospital owing to fatigue and tiredness during exercise for two weeks. She had been diagnosed with autoimmune hemolytic anemia before and did not comply with the treatment. This patient has been reevaluated of having AIHA from the symptoms of fatigue, enlarged spleen, low hemoglobin, increased reticulocytes, signs of hemolytic in blood smear examination, increased indirect bilirubin, LDH and the Combs’ test result was given positive. She received methylprednisolone 2 mg/kg of body weight intravenously, washed packed red cells (PRC), calcium and proton pump inhibitor. She was discharged at the seventh day since admission and she was prescribed oral methylprednisolone equal to 1 mg/kg body weight.Conclusion : This is an educated case of non-compliance of AIHA that should be given high dose steroid and blood transfusion during hospitalization amid the COVID-19 pandemic. The recommendation of treatment for AIHA was still the same as before the pandemic occured.